Adipocyte Metabolic Pathways Regulated by Diet Control the Female Germline Stem Cell Lineage in Drosophila melanogaster. Issue 2 (1st June 2017) - Matsuoka, Shinya; Armstrong, Alissa R; Sampson, Leesa L; Laws, Kaitlin M; Drummond-Barbosa, Daniela
Abstract: Two papers in this issue demonstrate novel proteomic approaches that enhance genetic analysis. Matsuoka et al. investigated how diet-regulated........ Nutrients affect adult stem cells through complex mechanisms involving multiple organs. Adipocytes are highly sensitive to diet and have key metabolic roles, and obesity increases the risk for many cancers. How diet-regulated adipocyte metabolic pathways influence normal stem cell lineages, however, remains unclear. Drosophila melanogaster has highly conserved adipocyte metabolism and a well-characterized female germline stem cell (GSC) lineage response to diet. Here, we conducted an isobaric tags for relative and absolute quantification (iTRAQ) proteomic analysis to identify diet-regulated adipocyte metabolic pathways that control the female GSC lineage. On a rich (relative to poor) diet, adipocyte Hexokinase-C and metabolic enzymes involved in pyruvate/acetyl-CoA production are upregulated, promoting a shift of glucose metabolism toward macromolecule biosynthesis. Adipocyte-specific knockdown shows that these enzymes support early GSC progeny survival. Further, enzymes catalyzing fatty acid oxidation and phosphatidylethanolamine synthesis in adipocytes promote GSC maintenance, whereas lipid and iron transport from adipocytes controls vitellogenesis and GSC number, respectively. These results show a functional relationship between specific metabolic pathways in adipocytes and distinct processes in the GSC lineage, suggesting the adipocyte metabolism–stem cell link as an important area of investigation in other stem cell systems.